Morpho-taxonomy of Corycaeid Cyclopoids from Lakshadweep Sea, South Eastern Arabian Sea—A Part of the Indian Ocean. - Radhika, S.R. & S.B. Nandan [S. Bijoy Nandan] (In: Pandey D., M. Ravichandran & N.Nair (eds) Dynamics of the Earth System: Evolution, Processes and Interactions. Society of Earth Scientists Series. Springer, Cham, 2020)
Classical taxonomy, the science of naming and classifying organisms accurately plays an important role in biodiversity conservation. Taxonomy has been endorsed as an important gadget for the execution and monitoring of the Convention on Biological Diversity which in turn has significantly reformed the climate in the field of taxonomic research. This paper endeavor to accomplish the goal of strengthening capacity building (taxonomists) as a part of Global Taxonomy Initiative of convention on biological diversity and also due to rapidly dwindling cyclopoid copepod taxonomic expertise in the national scenario. Despite the vastness of the volumes of seas and oceans in this world, the echelon of work done on the taxonomical facet of marine cyclopoid copepods are surprisingly fewer. Since the taxonomy of marine cyclopoids along the southwestern part of Indian Ocean have not been attempted much in the Indian scenario, the present study grips much significance as it becomes a pioneering effort on the morphotaxonomy of Corycaeid copepods (Order: Cyclopoida) from Lakshadweep Sea and associated islands, South Eastern Arabian Sea—a part of Indian Ocean. Sampled small Corycaeidae group of copepods in high abundance from five lagoons (Kavaratti, Kalpeni, Minicoy, Agatti and Bangaram) and open ocean zones of Minicoy of the Lakshadweep archipelago during premonsoon, monsoon and post monsoon seasons during 2013–2016 period thus handing over the morphotaxonomic descriptions of twenty-three species under five genera (Corycaeus, Urocorycaeus, Onychocorycaeus, Ditrichocorycaeus and Farranula) belonging to the family Corycaeidae.